Kommunikation, Jurisdiktion, Integration das Papsttum und das Erzbistum Toledo im 12. Jahrhundert (ca. 1085 - ca. 1185) - Holndonner, Andreas (Berlin München [u.a.] De Gruyter Akademie Forschung, 2014)
The Middle Ages are justifiably regarded as an epoch characterized by fundamental integration processes, in which the papacy played a key role. This volume analyzes the changing relations of the Popes to the Archdiocese of Toledo, located directly on the frontier of the Moslem-ruled southern portion of the Iberian Peninsula, in a case study on papally influenced integration processes during the 12th century.--
Text dt., Quellen teilw. lat. - Quellen- und Literaturverz. S. [629] - 697
Vollst. zugl.: Erlangen-Nürnberg, Univ., Diss., 2012
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Catholic Church -- Archdiocese of Toledo (Spain) -- History; Papacy -- History -- To 1309; Konferenzschrift; Hochschulschrift